Perancangan Alat Pirolisis Limbah Plastik Menjadi Bahan Bakar Alternatif - Rif’an Arif; Tulus Subagyo (CV. IRA PUBLISHING, 2025)
This research discusses the design and testing of a simple, economical pyrolysis device for converting plastic waste into an alternative fuel. The pyrolysis device measures 1000 mm × 700 mm × 580 mm, with a reactor constructed from a used 12-kg LPG cylinder, equipped with a steam delivery pipe, a two-coil spiral condenser, and other supporting components. Test results indicate a device performance of 0.000005 liters/h, indicating that the device is still operating on a small scale with low efficiency. The volume of liquid smoke produced reaches 3.26 m³/kg based on the assumed water vapor density. Recommendations for development include optimizing the condenser design, adding thermal insulation, using more comprehensive measuring instruments, and testing various temperatures and plastic types to improve efficiency. This research is the first step toward using plastic waste to produce valuable alternative fuels.